Упрощение выражений: 1) 3(х + 6) – х – 2(х + 9) = 2) 6 – 3(х + 1) – (7 – х) =

0 голосов
825 просмотров

Упрощение выражений: 1) 3(х + 6) – х – 2(х + 9) = 2) 6 – 3(х + 1) – (7 – х) =


Математика (30 баллов) | 825 просмотров
Дано ответов: 2
0 голосов

Ответ:

Пошаговое объяснение:

1) 3(х + 6) – х – 2(х + 9) = 3х+18-х-2х-18=

0

2) 6 – 3(х + 1) – (7 – х) =6-3х-3-7+х=-2х-4

(123k баллов)
0

спасибо

0

Пожалуйста

0 голосов

1) 3(х+6)-х-2(х+9)=?

3х+18-x-2x-18=?

3x-x-2x=18-18

0=0

2) 6-3(x+1)-(7-x)=?

6-3x-3-7+x=?

-4-2x=?

-2x=4

x=-2

(523 баллов)